The Economic Impact Analysis of Infrastructure Development in East Java: Do Roads Drive Growth? - Rachmad Kresna Sakti; Eddy Suprapto; Axellina Muara Setyanti (Journal of International Conference Proceedings (JICP), 2022)
Infrastructure development is considered as a locomotive that accelerates the pace of the economy in a region. The success of the development process is generally measured by economic growth. This study aims to analyze the effect of road infrastructure development on the economic growth of districts/cities in East Java and identify differences in the economic growth of East Java districts/cities before and after road infrastructure development. To answer the first research objective, panel data regression was used in 38 districts/cities in East Java with the dependent variable being economic growth, and the independent variable measuring the availability of infrastructure. Furthermore, to answer the second research objective, paired t-test was used. Road infrastructure, as well as government spending on public services and capital were found affecting economic growth at a decreasing rate. Tax revenue found to boost economic growth, implying that tax still one of the main instrument driving growths. Lastly, during the development of infrastructure, no significant difference has been found in economic growth. Indicates that the development effect on growth is a long-term effect. The results contribute to the discussion regarding the determinants of regional economic growth and how development can affect the economic growth of one or more regions. Keywords: Economic Growth, Infrastructure, East Java.